Ca2+/Calmodulin-Dependent Protein Kinase II (CaMKII) Regulates Basal Cardiac Pacemaker Function: Pros and Cons - Tatiana M. Vinogradova; Edward G. Lakatta (Cells)
The spontaneous firing of the sinoatrial (SA) node, the physiological pacemaker of the heart, is generated within sinoatrial nodal cells (SANCs) and is regulated by a “coupled-clock” pacemaker system, which integrates a “membrane clock”, the ensemble of ion channel currents, and an intracellular “Ca2+ clock”, sarcoplasmic reticulum-generated local submembrane Ca2+ releases via ryanodine receptors. The interactions within a “coupled-clock” system are modulated by phosphorylation of surface membrane and sarcoplasmic reticulum proteins. Though the essential role of a high basal cAMP level and PKA-dependent phosphorylation for basal spontaneous SANC firing is well recognized, the role of basal CaMKII-dependent phosphorylation remains uncertain. This is a critical issue with respect to how cardiac pacemaker cells fire spontaneous action potentials. This review aspires to explain and unite apparently contradictory results of pharmacological studies in the literature that have demonstrated a fundamental role of basal CaMKII activation for basal cardiac pacemaker function, as well as studies in mice with genetic CaMKII inhibition which have been interpreted to indicate that basal spontaneous SANC firing is independent of CaMKII activation. The assessment of supporting and opposing data regarding CaMKII effects on phosphorylation of Ca2+-cycling proteins and spontaneous firing of SANC in the basal state leads to the necessary conclusion that CaMKII activity and CaMKII-dependent phosphorylation do regulate basal cardiac pacemaker function.